TINGKAT KEKERABATAN DAN WAKTU PISAH ANTARA BAHASA ACEH DAN SUNDA: KAJIAN LINGUISTIK HISTORIS KOMPARATIF - Al Quds, Nabil Asad (Prosiding Seminar Nasional Bahasa Ibu; Vol 2 No 1 (2025): Prosiding Seminar Nasional Bahasa Ibu 2024/2025, 2025)
This research aims to examine the degree of linguistic relatedness, divergence time, and phonemic correspondence between the Acehnese and Sundanese languages. The research data consist of 200 Swadesh vocabulary items in Acehnese and Sundanese. The data types include primary data obtained through interviews with native speakers of both languages and secondary data derived from literature reviews of Acehnese and Sundanese dictionaries. The research employs both qualitative and quantitative methods, utilizing lexicostatistics and glottochronology techniques. The results indicate that Acehnese and Sundanese are related languages, with a linguistic relatedness percentage of 46%, placing them within the same language family. Acehnese and Sundanese were once a single language before 83–530 CE, or approximately 1,941–1,494 years ago, before they diverged after 83–530 CE. Additionally, at least three pairs of phonemic correspondences in vowels and one pair in consonants were identified between the two languages.